Quantification of seasonal-long physical load in soccer players with different starting status from the English Premier League: Implications for maintaining squad physical fitness - Anderson, L.; Orme, P.; Di Michele, R.; Close, G. L.; Milsom, J.; Morgans, R.; Drust, B.; Morton, J. P. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To quantify the accumulative training and match load during an annual season in English Premier League soccer players classified as starters (n = 8, started =60% of games), fringe players (n = 7, started 30-60% of games) and nonstarters (n = 4, started <30% of games).